A SHORT LOOK AT MICROBIAL PRODUCERS OF BIOBUTANOL – NEW TRENDS, POTENTIALITIES AND LIMITATIONS - Kregiel, Prof. Dorota (Journal on Processing and Energy in Agriculture, 2021)
Butanol production by microorganisms was first reported by Louis Pasteur in 1861. However, it was not until 60 years later that Chaim Weizmann used anaerobic bacteria of the genera Clostridium for butanol production on a large scale. Interest in acetone-butanol-ethanol fermentation was developed in the 1980s, due to the escalating price of petroleum. Nowadays, the energy crisis, climate change and greenhouse effect have created strong demand for the development of alternative energy sources. Researchers have made an attempt to produce biobutanol from various second-generation feedstocks with new microbial strains and new technologies. The use of numerous waste materials, improved strains and co-cultivation have the potential to improve butanol yield. This paper is dedicated to reviewing recent advances in butanol production by microorganisms.